2016
DOI: 10.1016/j.jcf.2015.06.007
|View full text |Cite
|
Sign up to set email alerts
|

A semi-blinded study comparing 2 methods of measuring nasal potential difference: Subcutaneous needle versus dermal abrasion

Abstract: Both NPD methods are similar in terms of discriminative value and subject's preference, comparing classical CF and HV. For diagnosing CF, the operator's preferred NPD-method may be used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…We used a dermal abrasion because it was validated in our institution and because of the operator's expertise. De Watcher et al reported both methods are similar and acceptable suggesting that the operators preferred NPD-method should be used [29]. (iii) The final NPD step with an ATP-solution was not performed.…”
Section: Discussionmentioning
confidence: 99%
“…We used a dermal abrasion because it was validated in our institution and because of the operator's expertise. De Watcher et al reported both methods are similar and acceptable suggesting that the operators preferred NPD-method should be used [29]. (iii) The final NPD step with an ATP-solution was not performed.…”
Section: Discussionmentioning
confidence: 99%
“…NPD is an indirect assessment of the ion transport in the nasal airway epithelia: the change in voltage reflecting the change in current. The technique was first described by Knowles et al [108], and was subsequently optimized and standardized [109][110][111][112][113][114].…”
Section: Nasal Potential Difference (Npd)mentioning
confidence: 99%